Kompetensi Auditor Sebagai Faktor Pendukung Audit Investigasi - Tiara Fibrianti Ning Tyas; Gideon Setyo Budiwitjaksono (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Fraud detection is urgent for many companies or agencies. Cases of fraud and irregularities are increasingly rampant in Indonesia. Cases of corruption, misappropriation of assets, abuse of authority, and fraudulent financial statements often occur in various government agencies and companies. This study aims to determine auditor competence as a supporter of investigative audits. An interpretive qualitative method with a phenomenological approach was used in this study. Data collection techniques were carried out through interviews and observation. Data analysis was carried out by compiling questions, recording interview results, and analyzing and organizing them. The results showed that auditor competence has an influence on investigative audits. Qualified forensic analysis skills, interview skills to obtain information, and critical thinking to solve every problem in the field. Auditor competence in terms of understanding and knowledge related to regulations and laws is very important because it is the basis or guideline for conducting investigative audits. Because auditor competence is an important factor in supporting investigative audits, competency development is very necessary. Training, seminars, or continuing education can be a form of development that can be implemented by auditors. Qualified competence will improve the quality of the audit.